(untitled) (Indian Journal of Forensic Medicine & Toxicology, 2020)
Background: Cigarette smoking is the largest preventable risk factor for morbidity and mortality in developed countries. Healthcare providers who smoke are less likely to advise patients to quit smoking. Being a female and smoker adding more burdens on society. The obkecibe o the studu is to assess the prevalence of smoking among Iraqi female medical provider.A descriptive cross-sectional study with an analytic element. Data collection was done via electronic questionnaire forms distributed online to contact list for 450 -easy to reach- female health providers (doctors, dentists, pharmacists) who work in different hospitals, PHCs and health institutes in Iraq.Nearly 15.3% of the samples were smokers, 53% of sample was 20-29 years while nearly 62% of sample was married. About two third of sample had bachelor degree (66.2) while nearly half of the sample (52.9) were doctors. Regarding the place of work about (55.6) of sample were working in hospital and the years of service were equally distributed between <5 years and >5 years. Nearly half of the sample has husbands or friends who are smokers. The smoking environment was significantly affecting the smoking status while there is no association between age, marital status, education, field of work, place of work and years of service.The percentage of female smokers among medical service providers is high, and female doctors got the highest rate. With regard to age, the age group between 20-29 was the highest among female smokers. The results also showed a higher percentage among those who work in hospitals, and the largest proportion of female smokers was among those who had spouses or friends who smoked.